Discoveries in North-Western Wigtownshire: Cinerary and Incense-Cup Urns and Perforated Axe-Hammer; Mould for Bronze-Winged Chisel; Whetstone for Stone Axes; Cup-marked Rocks and Boulder; Apron of Moss Fibres - Mann, Ludovic McLellan (Proceedings of the Society of Antiquaries of Scotland, 1923)
A cinerary urn containing cremated bone and charcoal was recovered from a previously disturbed burial. An accompanying incense cup contained larger fragments of bone and charcoal. The bones in the latter were those of a child while the bones in the former could not be identified. The pit had been lined with stones. An axe hammer and mould were found a short distance away. The mould is of an unusual type while parallels for the axe hammer are presented. An 'apron' made from moss fibres was found close to a cairn.